Assessment of multiple hormone activities of a UV-filter (octocrylene) in zebrafish (Danio rerio). (September 2016) - Zhang, Qiuya Y.; Ma, Xiaoyan Y.; Wang, Xiaochang C.; Ngo, Huu Hao
Abstract: In this study, zebrafish ( Danio rerio ) were exposed to a UV-filter-octocrylene (OCT) with elevated concentrations for 28 d. The total body accumulation of OCT in zebrafish was found to reach 2321.01 ("L" level), 31, 234.80 ("M" level), and 70, 593.38 ng g −1 ("H" level) when the average OCT exposure concentration was controlled at 28.61, 505.62, and 1248.70 μg L −1, respectively. Gross and histological observations as well as RT-qPCR analysis were conducted to determine the effects of OCT accumulation on zebrafish. After exposure, the gonad-somatic index and percentage of vitellogenic oocytes were found to increase significantly in the ovaries of female zebrafish at the H accumulation level. Significant up-regulation of esr1 and cyp19b were observed in the gonads, as well as vtg1 in the livers for both female and male zebrafish. At M and H accumulation levels, apparent down-regulation of ar was observed in the ovaries and testis of the female and male zebrafish, respectively. Although the extent of the effects on zebrafish differed at different accumulation levels, the induction of vtg1 and histological changes in the ovaries are indications of estrogenic activity and the inhibition of esr1 and ar showed antiestrogenic and antiandrogenic activity, respectively. Thus, as OCT could easily accumulate in aquatic life such as zebrafish, one of its most of concern hazards would be the disturbance of the histological development and its multiple hormonal activities. Highlights: Octocrylene (OCT) can accumulate in fishes up to sufficiently high levels to cause adverse effects on the endocrine system. The accelerated ovary development indicates that OCT has the effect on sex-endocrinology. The gene alterations address that OCT has the multiple hormone activities.